2016
DOI: 10.1007/s10584-016-1695-0
|View full text |Cite
|
Sign up to set email alerts
|

500-yr. precipitation variability in Southern Taihang Mountains, China, and its linkages to ENSO and PDO

Abstract: An annually resolved and absolutely dated ring-width chronology spanning 657 yrs. is constructed with Whitebark pine (Pinus bungeana Zucc.) samples from the southern Taihang Mountains, Eastern China. On the basis of a significant correlation between the tree-ring width index and observed instrumental data, precipitation in current May is reconstructed for the region since AD 1510, with predictor variables accounting for 37.9 % of the variance in precipitation data.130 yrs cycles at the 95 % confidence level fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 52 publications
(50 reference statements)
4
10
1
1
Order By: Relevance
“…Spatial correlation of our reconstructed streamflow with SST and MTM spectral analysis results demonstrated the connections between June-July streamflow of the Weihe River and remote oceans (Figure 7 and Figure 8). Previous studies had reported that the dryness and wetness conditions in northern China including our Weihe River basin were related to the climate mode forcing, such as the Pacific Decadal Oscillation (PDO) and El Niño-Southern Oscillation (ENSO) [27][28][29][30]. Spatial correlation of our reconstructed streamflow with SST and MTM spectral analysis results demonstrated the connections between June-July streamflow of the Weihe River and remote oceans (Figures 7 and 8).…”
Section: Variation Features Of Streamflow Of the Weihe Riversupporting
confidence: 56%
“…Spatial correlation of our reconstructed streamflow with SST and MTM spectral analysis results demonstrated the connections between June-July streamflow of the Weihe River and remote oceans (Figure 7 and Figure 8). Previous studies had reported that the dryness and wetness conditions in northern China including our Weihe River basin were related to the climate mode forcing, such as the Pacific Decadal Oscillation (PDO) and El Niño-Southern Oscillation (ENSO) [27][28][29][30]. Spatial correlation of our reconstructed streamflow with SST and MTM spectral analysis results demonstrated the connections between June-July streamflow of the Weihe River and remote oceans (Figures 7 and 8).…”
Section: Variation Features Of Streamflow Of the Weihe Riversupporting
confidence: 56%
“…Twelve El Niño events occurring in the reconstructed drought index series accounted for 38.71% of the extreme dry years, while nine La Niña events accounted for 31.03% of the extreme wet years. Similar cycles related to ENSO have been revealed in other tree-ring climate variable reconstruction series in surrounding regions [11,15,16,34,51,52].…”
Section: Regional Drought Signals and Teleconnectionsupporting
confidence: 77%
“…Considering the TRW series of P. tabuliformis in Baiyunshan and Longchiman are mainly restricted by the early summer moisture conditions, we hypothesize that the early summer hydroclimatic signals might be strengthened only using EWW, since earlywood is mostly formed before mid-July (Zhang et al, 1982). Therefore, the objectives of this study are (1) to verify that EWW is more sensitive to early summer hydroclimatic factors than TRW and LWW for P. tabuliformis at Baiyunshan and Longchiman, (2) to reconstruct early summer hydroclimate variations using EWW, and (3) to tentatively explore the relationship between the reconstructed hydroclimate variability and EASMI.…”
Section: Introductionmentioning
confidence: 98%